Update to the Treatment of Parkinson’s Disease Based on the Gut-Brain Axis Mechanism - Sun, Xiaohui; Xue, Li; Wang, Zechen; Xie, Anmu (Frontiers in Neuroscience, 2022)
Gastrointestinal (GI) symptoms represented by constipation were significant non-motor symptoms of Parkinson’s disease (PD) and were considered early manifestations and aggravating factors of the disease. This paper reviewed the research progress of the mechanism of the gut-brain axis (GBA) in PD and discussed the roles of α-synuclein, gut microbiota, immune inflammation, neuroendocrine, mitochondrial autophagy, and environmental toxins in the mechanism of the GBA in PD. Treatment of PD based on the GBA theory has also been discussed, including (1) dietary therapy, such as probiotics, vitamin therapy, Mediterranean diet, and low-calorie diet, (2) exercise therapy, (3) drug therapy, including antibiotics; GI peptides; GI motility agents, and (4) fecal flora transplantation can improve the flora. (5) Vagotomy and appendectomy were associated but not recommended.